Circadian and Sleep Metabolomics Across Species. Issue 12 (29th May 2020) - Malik, Dania M.; Paschos, Georgios K.; Sehgal, Amita; Weljie, Aalim M.
Abstract: Under normal circadian function, metabolic control is temporally coordinated across tissues and behaviors with a 24-h period. However, circadian disruption results in negative consequences for metabolic homeostasis including energy or redox imbalances. Yet, circadian disruption has become increasingly prevalent within today's society due to many factors including sleep loss. Metabolic consequences of both have been revealed by metabolomics analyses of circadian biology and sleep. Specifically, two primary analytical platforms, mass spectrometry and nuclear magnetic resonance spectroscopy, have been used to study molecular clock and sleep influences on overall metabolic rhythmicity. For example, human studies have demonstrated the prevalence of metabolic rhythms in human biology, as well as pan-metabolome consequences of sleep disruption. However, human studies are limited to peripheral metabolic readouts primarily through minimally invasive procedures. For further tissue- and organism-specific investigations, a number of model systems have been studied, based upon the conserved nature of both the molecular clock and sleep across species. Here we summarize human studies as well as key findings from metabolomics studies using mice, Drosophila, and zebrafish. While informative, a limitation in existing literature is a lack of interpretation regarding dynamic synthesis or catabolism within metabolite pools. To this extent, future work incorporating isotope tracers, specific metabolite reporters, and single-cell metabolomics may provide a means of exploring dynamic activity in pathways of interest. Graphical Abstract: Unlabelled Image Highlights: Circadian clocks regulate various metabolic processes across species. Sleep is essential across organisms, yet the metabolic role is not well understood. Altered circadian rhythmicity and sleep result in metabolic changes across species. Metabolomics approaches have provided insight into circadian and sleep processes. Metabolic flux is not yet recapitulated in high resolution circadian studies.